Intercultural communication competence development through student mobility programmes and through internationalisation at home - Elena Yu. Makeeva; Natasha Gousseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper assumes that internationalisation of higher education demands a variety of pedagogical approaches to facilitate every student’s acquisition of intercultural competencies. Drawing from two existing internationalisation approaches, it is argued that intercultural communication - both as a field of study and a discipline - can also play a key role in this process. Only graduates who possess intercultural communication competence as well asknowledge and such skills as cultural awareness, second language acquisition, and interaction across cultures will be able to live and work more effectively in a diverse and global environment.